The Transformation of Aqidah Akhlak Learning Through Active Learning Strategies to Promote Meaningful Learning - Muhammad Akhwanul Mukhlasin; Layla Mardliyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The transformation of Islamic education requires learning approaches that not only focus on knowledge acquisition but also support students in understanding, internalizing, and applying religious values in their daily lives. In Akidah Akhlak learning, a gap remains between students’ theoretical understanding of religious concepts and their ability to relate these values to real-life experiences. This study aims to analyze the transformation of Akidah Akhlak learning through active learning strategies in achieving meaningful learning. This research employed a qualitative approach with a descriptive design conducted at MTs Al-Hidayah Purwokerto. The research subjects consisted of an Akidah Akhlak teacher and eighth-grade students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the implementation of active learning through group discussions, Problem Solving, Gallery Walk, and Market Place Activity transforms Akidah Akhlak learning from teacher-centered instruction into a more participatory, collaborative, and reflective process. Furthermore, these strategies contribute to the development of meaningful learning by enabling students to connect new knowledge with previous experiences, understand the relevance of Akidah Akhlak values, and reflect on their application in everyday life. This study highlights that active learning functions not merely as a strategy to increase student participation but as a transformative pedagogical approach for developing deeper understanding and value internalization in Islamic education.